Operative vaginal deliveries and their impact on maternal and neonatal outcomes - prospective analysis - Morávková, P; Hruban, L; Jančářová, D; Janků, P; Gerychová, R; Vinklerová, P; Štěpánová, R; Ventruba, P (Ceska gynekologie, 2019)
OBJECTIVE: Evaluation of maternal and neonatal outcomes in operative vaginal deliveries in prospective study analysis. DESIGN: Prospective case-control study analysis. SETTING: Prospective analysis of 292 operative vaginal deliveries (VEX, forceps) for the period June 2016 - August 2017 from overall 6056 vaginal deliveries. Type and frequency of maternal and neonatal trauma occurence was observed in connection with using vacuum-assisted delivery and forceps delivery, mainly the cephalohematomas and their complications. Collected data were statistically analysed. RESULTS: In the reported period from overall 6056 deliveries there were 216 vacuumextractions (3.6%) and 72 forceps deliveries (1.2%) performed. Both methods were used in four patients (VEX and forceps). The most frequent trauma in newborns were cephalohematomas. Remarkable cephalohematoma, requiring further observation has occured in 40 newborns (18.5%) after vacuum-assisted delivery and in 5 newborns (6.9%), (p = 0,017) after forceps delivery. Consequential punction of cephalohematoma occured only after vacuumextraction delivery and in 6 newborns (15.0 %). The third degree perineal rupture occured after vacuumextraction in 20 patients (9.3%) and after forceps delivery in 12 patients (16.7%), (p = 0,091). The fourth degree perineal rupture occured only after vacuumextraction and in 1 case (0.5%). CONCLUSION: The vacuumextraction compared with forceps is more likely to be associated with the statistically significant incidence of cephalohematomas and their further treatment. Forceps deliveries compared with vacuumextraction are more likely to be associated with the maternal perineal trauma, but the diference was not statistically significant.
Keywords: vacuum-assisted delivery; novorozenec; Infant, Newborn; výsledek těhotenství; Pregnancy; Humans; Case-Control Studies; cephalohematoma; vakuová extrakce porodnická; forceps delivery; studie případů a kontrol; Female; Pregnancy Outcome; lidé; Genitalia, Female; maternal trauma; hematom; lacerace; ženské pohlaví; ženské pohlavní orgány; vedení porodu; porodnické kleště; Delivery, Obstetric; Lacerations; těhotenství; Birth Injuries; Vacuum Extraction, Obstetrical; prospektivní studie; Hematoma; Obstetrical Forceps; neonatal trauma; porodní poranění novorozence; Prospective Studies